Evaluation of the Socio-Economic Factors Impeding Production of Cashew in Ogaji, North Central Nigeria - Uсhе Okoуе; Success Esomchi Obi; Okeme Ukwumonu Patrick (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
The paper examined socio-economic factors affecting cashew production in Ogaji, Ankpa LGA, Northcentral Nigeria. Data was collected through a semi-structured questionnaire and interview administered to 143 registered farmers. Data obtained were analyzed descriptively using inferential statistics of mean score ranking, frequency tables and graph. Results showed that majority of the farmers were within the age of 26-35 and have been into farming since birth. Also there was moderate literacy level among the farmers as 50% of total respondents have formal education. Findings reveals that the socio-economic factor affecting production were; Access to and use of credit facilities, farmers-herders conflict, income level, transportation problem, lack of access to capital and poor extension services agent relations were the major socio-economic factors affecting cashew production in the study area. The study amongst others recommends that; the government should encourage private sectors such as Non-Governmental Organizations (NGOs) to invest in credits facilities like small-scale bank to offer credit to farmers at affordable rate, proactive measures should be taken to quell the farmer-herders crisis as it poses threat to farming activities. Government should strive to develop roads; this will increase small holder’s economic opportunities by reducing transport cost and allowing farmers to get access to marketing information and small holder’s cashew profitability. Extension service agent should try to understand the rural dwellers and their educational level to help them have access to extension services in other to improve their knowledge of farm management.